Injury and illness in aquatic sport: how high is the risk? A comparison of results from three FINA World Championships. Issue 4 (16th June 2016) - Prien, Annika; Mountjoy, Margo; Miller, Jim; Boyd, Kevin; van den Hoogenband, Cees; Gerrard, David; Cherif, Mohamed Yahia; Lu, Yifan; Nanousis, Kyriakos; Ortiz Liscano, Edgar Ivan; Shahpar, Farhad Moradi; Junge, Astrid
Abstract : Background: Epidemiological information on injury/illness is required to develop effective injury prevention strategies. Aim: To assess the frequency and characteristics of injuries/illnesses (1) in the 4 weeks prior to and (2) during the Fédération Internationale de Natation (FINA) World Championships 2015 compared with 2013 and 2009. Method: (1) Athletes answered a retrospective questionnaire, and (2) the medical staff reported injuries/illnesses prospectively during the championships. Results: (1) A quarter of responding athletes reported symptoms in the 4 weeks prior to the championships. More than half of all affected athletes presented with substantial severity, 80% took medication, 70% had overuse injuries and 30% did not modify their training regime despite symptoms. At the start of the championships, 70% of affected participants were still symptomatic. (2) During the championships, injury and illness incidence was 12.9 per 100 athletes. The most common injuries were shoulder sprains (5.7%) and muscle cramps of the lower back (5.7%). The most common illnesses were infections of the respiratory (33.9%) and gastrointestinal tract (23.5%). Risk factors included discipline and age, but not gender. Incidence was highest in athletes competing in high diving (HD), water polo (WP) and diving (DIV) for injuries, and WP and swimming (SW) for illnesses. The significantly higher incidence of injuries and illnesses at the FINA World Championships 2015 compared with 2013 and 2009 was most probably due to a similarly improved response rate of the medical staff. Conclusions: In aquatic sports, surveillance and health promotion should focus on prevention of out-of-competition overuse injuries and athlete education.